Transfusion-transmissible infections among blood donors in Kathmandu, Nepal - Ashish Chandra Shrestha; Prakash Ghimire; Bishnu Raj Tiwari; Manita Rajkarnikar (Journal of Infection in Developing Countries)
Background: Screening of transfusion-transmissible infections (TTIs) among blood donors can be a cost-effective approach to monitor the prevalence, distribution, and trends of the infections among healthy-looking individuals. The study aimed to determine the seroprevalence of four TTIs, human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV) and syphilis, among blood donors in Kathmandu, Nepal.